Analisis Manajemen Program Relawan Pengajar Sinode GPM Pada Sekolah Dasar YPPK Kapahewa Dr. JB Sitanala Klasis Seram Utara Barat: Management Analysis of GPM Synod Volunteer Teaching Program at YPPK Kapahewa Elementary School, Dr. JB Sitanala Klasis, North West Seram - Solissa, Risma Jaftien; Wenno, Izaak H; Papaliya, Josef (ITScience (Information Technology and Science), 2024)
This study aims to analyze the management of the GPM Synod Volunteer Teaching Program at SD YPPK Kapahewa from the aspects of planning, organizing, implementing, supervising, as well as supporting and inhibiting factors that affect program control. The method used is qualitative with interview, observation, and documentation techniques. The subjects of the study included volunteers, principals, teachers, volunteer mentors, and students. The results of the study indicate that: i) the planning program includes a structured volunteer recruitment, provisioning, distribution process; ii) the organization of the program runs effectively with a clear structure and good communication between volunteers, teachers, and principals; iii) the implementation of the program challenges discipline, but collaboration between volunteers and the school continues to run well; iv) program supervision is carried out through periodic monitoring and evaluation by the GPM Synod; v) supporting factors include financial support and volunteer motivation, while inhibiting factors are low school discipline and interest in volunteer registration. This study provides suggestions for improving the quality of the management program, including strengthening volunteer training and closer collaboration with the local community.